Influence of the surface electronic processes on the spectrometric characteristics of silicon detectors - Gaidar, G.P.; Berdnichenko, S.V.; Vorobyov, V.G.; Kochkin, V.I.; Lastovetskiy, V.F.; Litovchenko, P.G. (Вопросы атомной науки и техники, 2016)
In this paper the features of influence of the surface electron processes on the formation of silicon surface-barrier detector structures were founded, the regimes of chemical treatments of the surface for Si crystals were established with using of different combinations of etchants for the accelerated creation of surface-barrier structures with stable parameters, the slow regimes of etching were developed for making the detectors of plane-parallel geometry. On the basis of experimental studies concerning the improvement of the formation processes of qualitative surface-barrier structures, the fabrication technique of the silicon spectrometric detectors was optimized; the prototypes were manufactured and their characteristics were identified.